2018
DOI: 10.1128/iai.00892-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Inducible Adhesin CpAls7 in Binding of Candida parapsilosis to the Extracellular Matrix under Fluid Shear

Abstract: The yeast, , is an increasingly common cause of systemic fungal infections among the immune compromised, including premature infants. Adhesion to host surfaces is an important step in pathogenesis, but this process has not been extensively studied in this organism. A microfluidics assay was developed to test the ability of to adhere to immobilized host extracellular matrix proteins under physiologic fluid shear conditions. Growth in mammalian tissue culture media at 37°C for 3-6 hours led to induction of an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…Als proteins are adhesins, yet function promiscuously, so looking toward shared function as the means for assigning names is also not an effective method. Some authors have referred to ALS genes using the label assigned in the annotation of the representative genome assembly (Bertini et al, 2016; Neale et al, 2018; Zoppo et al, 2018). This appealing approach provides a unique name for each gene and, like a street address, communicates physical location information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Als proteins are adhesins, yet function promiscuously, so looking toward shared function as the means for assigning names is also not an effective method. Some authors have referred to ALS genes using the label assigned in the annotation of the representative genome assembly (Bertini et al, 2016; Neale et al, 2018; Zoppo et al, 2018). This appealing approach provides a unique name for each gene and, like a street address, communicates physical location information.…”
Section: Discussionmentioning
confidence: 99%
“…Bertini et al (2016) showed that deletion of CpALS4800 resulted in a C. parapsilosis strain with reduced adhesion to human buccal epithelial cells. Neale et al (2018) documented a role for CpAls4800 in adhesion of C. parapsilosis to extracellular matrix proteins in a microfluidics assay using physiological fluid shear conditions. Zoppo et al (2018) deleted CoALS4210 and showed decreased adhesion to human buccal epithelial cells for the resulting C. orthopsilosis mutant strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. parapsilosis ortholog of CaALS7 is a key determinant for adhesion to host epithelial cells, as gene disruption led to a decreased ability to adhere to human buccal epithelial cells and also resulted in decreased virulence in vivo (129). CpALS7 is also necessary for C. parapsilosis to adhere to host ECM proteins under shear force (159). Additionally, C. parapsilosis cells require the presence of calcium, glutamic acid, and proline for adherence under shear flow conditions.…”
Section: Molecular Mechanisms Of C Parapsilosis Virulence Adhesionmentioning
confidence: 99%
“…This feature is highly variable among individual clinical isolates [ 13 ]. In C. parapsilosis , the formation of biofilms is associated with the ability to form pseudohyphae [ 14 , 15 , 16 ] as well as the concomitant change in expression levels of cell wall-localized adhesins such as Als1-7 [ 17 , 18 , 19 ] or Rbt1 [ 20 ]. Importantly, susceptibility to commonly used azole-based antifungal agents in fungal biofilms on medical devices may be strongly reduced [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%